Strategi Peningkatan Publikasi Ilmiah Melalui Pelatihan Kompetensi Publikasi bagi Kepala Madrasah - syibranmulasi; Suriana; Rahmat Saputra (Journal of Community Dedication and Development (Pengabdian Kepada Masyarakat), 2024)
Scientific publications play an important role in education, especially for teachers who want to contribute to the development of science and teaching practices. For madrasah teachers, the ability to publish research results and teaching experiences not only increases professional credibility but also enriches the educational literature. Therefore, strategies to improve scientific publications through publication competency training become very relevant. This training aims to develop madrasah teachers' competence in scientific publications, especially in publishing articles in accredited journals. The training implementation method includes theoretical and practical sessions designed to provide an in-depth understanding of the process of writing, editing, and publishing scientific papers. During the day, participants will be mentored by experts in the field of scientific publications, who will provide comprehensive materials and practical guidance. The results of this training showed an increase in teachers' understanding of the importance of scientific publications and technical skills in writing and publishing articles in accredited journals. In addition, the training successfully established a collaborative network between schools and universities, both in Aceh and at the national level. This network is expected to support the continuous development of teachers' competencies and expand their access to academic resources. Thus, this publication competency training for madrasah teachers not only improves the ability of individual teachers in scientific publications, but also strengthens the relationship between educational institutions, thus creating synergy for the advancement of education in Indonesia